2016
DOI: 10.1177/0958928716633044
|View full text |Cite
|
Sign up to set email alerts
|

Welfare, labour market deregulation and households’ poverty risks: An analysis of the risk of entering poverty at childbirth in different European welfare clusters

Abstract: This article deals with families' risk of entering poverty as a consequence of childbirth in four European Union (EU) welfare clusters. Poverty risks around childbirth are institutionally stratified according to specific characteristics of national welfare systems and the value they assign to family policies as well as the kind of labour market deregulation. While southern European countries are known for having welfare systems that make few provisions for 'the future generations of citizens', conservative and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 68 publications
2
32
0
1
Order By: Relevance
“…Since the introduction of these contracts, the traditional division between insiders and outsiders in the labour market has been reinforced among the young. The ample sociological literature on the topic, however, raises doubts about the effectiveness of the deregulation undergone in recent decades (Barbieri and Sestito 2008;Barbieri and Scherer 2009;Cutuli and Guetto 2013;Barbieri et al 2015; Barbieri and Bozzon 2016). These authors demonstrated that the process of partial and targeted labour market deregulation, indeed, did not increase the (net) amount of occupation by creating additional jobs, but rather replaced secure, unionized labour with precarious, cheaper employment.…”
Section: The Italian Settingmentioning
confidence: 99%
“…Since the introduction of these contracts, the traditional division between insiders and outsiders in the labour market has been reinforced among the young. The ample sociological literature on the topic, however, raises doubts about the effectiveness of the deregulation undergone in recent decades (Barbieri and Sestito 2008;Barbieri and Scherer 2009;Cutuli and Guetto 2013;Barbieri et al 2015; Barbieri and Bozzon 2016). These authors demonstrated that the process of partial and targeted labour market deregulation, indeed, did not increase the (net) amount of occupation by creating additional jobs, but rather replaced secure, unionized labour with precarious, cheaper employment.…”
Section: The Italian Settingmentioning
confidence: 99%
“…Social policies are a key matter for helping people overcome poverty and exclusion situations [40][41][42]. The social support variable was considered from the indicator [spr_exp_sum] from EUROSTAT Database [43].…”
Section: The Social Supportmentioning
confidence: 99%
“…But then again, it is striking that the 'market income poverty' -or poverty earnings, as we define it in this chapter -among single parents also varies so widely. In the absence of redistribution, single parents would be much more exposed to poverty in some countries than others (Barbieri & Bozzon, 2016). These cross-country differences relate to institutional and policy differences.…”
Section: Jeroen Horemans and Ive Marxmentioning
confidence: 99%
“…International studies do not draw straightforward conclusions when it comes to how the presence and generosity of benefits affect single mothers' employment (Destro & Brady, 2011). Barbieri and Bozzon (2016) show that pretransfer poverty risks of single parents are particularly high in social-democratic countries. Generous welfare provisions may play a role here, as they provide disincentives to work full time.…”
Section: Cross-country Variation In Single Parents' Employment Outcomesmentioning
confidence: 99%